The instruction myth : why higher education is hard to change, and how to change it - Tagg, John (Rutgers University Press, 2019)
Higher education is broken, and we haven't been able to fix it. Even in the face of great and growing dysfunction, it seems resistant to fundamental change. At this point, can anything be done to save it? The Instruction Myth argues that yes, higher education can be reformed and reinvigorated, but it will not be an easy process. In fact, it will require universities to abandon their central operating principle, the belief that education revolves around instruction, easily measurable in course syllabi, credits, and enrollments. Acclaimed education scholar John Tagg presents a powerful case that instruction alone is worthless and that universities should instead be centered upon student learning, which is far harder to quantify and standardize. Yet, as he shows, decades of research have indicated how to best promote student learning, but few universities have systematically implemented these suggestions. This book demonstrates why higher education must undergo radical change if it hopes to survive. More importantly, it offers specific policy suggestions for how universities can break their harmful dependence on the instruction myth. In this extensively researched book, Tagg offers a compelling diagnosis of what's ailing American higher education and a prescription for how it might still heal itself.
Keywords: Education, Higher -- Aims and objectives -- United States.; Universities and colleges -- United States -- Administration.; Educational change -- United States.; Enseignement supérieur -- Finalités -- États-Unis.; Enseignement -- Réforme -- États-Unis.; EDUCATION -- General.; Education, Higher -- Aims and objectives; Educational change; Universities and colleges -- Administration; United States; higher education, education, faculty, college, university, instruction, institution, education reform, student, professor, academia.